2021
DOI: 10.3390/ma14113072
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Nanohydroxyapatite-Enriched Hydrogen Peroxide Home Bleaching System on Color, Hardness and Microstructure of Dental Enamel

Abstract: This study aimed to evaluate two hydrogen peroxide (HP)-based at-home bleaching systems in order to analyze whether nano-hydroxyapatite (nHA) addition may represent a reliable and safe solution for tooth whitening without altering dental microstructure and hardness. Human third molars (N = 15) were treated with two bleaching agents, one containing 6%HP (6HP) and the other 6% HP nHA-enriched (6HP-nHA) with average particle diameter ranging from 5–20 nm. Their effects on enamel were assessed using a spectrophoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
0
10
0
2
Order By: Relevance
“…A previous study suggested that a clinically acceptable level of visual perception was possible when (∆E = 3.7) in the CIELab system [58]. This system contains three coordinates: L* which refers to the luminosity of the object and fluctuates from black to white; a* which indicates the chroma in the green-red axis; and the b* which represents the chroma in the axis of blue-yellow [60]. Each color has a numerical value, delivering an objective description [27].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that a clinically acceptable level of visual perception was possible when (∆E = 3.7) in the CIELab system [58]. This system contains three coordinates: L* which refers to the luminosity of the object and fluctuates from black to white; a* which indicates the chroma in the green-red axis; and the b* which represents the chroma in the axis of blue-yellow [60]. Each color has a numerical value, delivering an objective description [27].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined the effect of applying remineralization agents before, after, or before and after bleaching on the degree of color change in bovine teeth and reported that this did not alter the effectiveness of bleaching [11, 20, 36, 37]. It was also reported that the bleaching procedure applied with a bleaching gel mixed [16, 41] or enriched [36, 42] with various remineralizing agents achieved the same bleaching result as well as an additional protective effect. However, apart from the present study no ‘whiteness index’ study has been found in the literature, even though this is more appropriate for the evaluation of bleaching efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their effectiveness, peroxide-based products can cause severe abrasion of dental structures and are toxic/corrosive to any tissue in general. However, new studies highlighted that a low percentage of hydrogen peroxide, together with new nanofillers, allows for maintenance of enamel structure [ 4 ]. In this context, attempts are being made to develop whitening products with enzymatic action, which in some cases seem to be just as effective in removing extrinsic stains.…”
Section: Introductionmentioning
confidence: 99%